DEFINITION AND EXTRACTION OF FREE MONOSACCHARIDES FROM HELIANTHUS TUBEROSUS TUBER (Scientific journal of the Fergana State University, 2023)
The article focuses on the detection and isolation of free monosaccharides in  helianthus tuberosus tuber, as well as the subsequent use of the isolated substances for various purposes in the biotechnological and pharmaceutical industries. The results obtained during our experiments show that after the extraction process using ultrasound, we can see a significant increase in the amount of free fructose in the juice, i.e. F1 - 2.18%. In addition, a sample of the main juice was taken and the amount of free fructose was analyzed using a pH meter method, and  TSH and BH were also analyzed.